Cost and Time Efficiency Comparison of RISHA and Conventional Construction for Type 36 Post-Disaster Housing in Rua Village, Ternate - Rais D. Hi Yusuf; Joni Hermanto; Muhammad Yusri Abdul Gani (Equivalent: Jurnal Ilmiah Sosial Teknik, 2026)
Background: The increasing demand for rapid, affordable, and reliable housing has encouraged innovation in construction methods, including the RISHA modular system. However, its cost and time efficiency compared with conventional construction remain debated, especially in post-disaster and remote areas. Objective: This study aims to compare the construction costs and implementation time of the RISHA (Rumah Instan Sederhana Sehat) modular construction method and the conventional construction method for a Type 36 single-story house. Methods: This research employed a comparative quantitative approach. Data analysis included: (1) calculating work volume for each work category, (2) conducting unit price analysis based on the Ministry of Public Works and Housing’s Standard Unit Price Analysis (Analisis Harga Satuan Pekerjaan, AHSP) and Regional Standard Unit Prices (Harga Satuan Pokok Kegiatan, HSPK), (3) preparing the Cost Budget Plan (Rencana Anggaran Biaya, RAB), and (4) calculating implementation time using the work coefficient method. Results: The results show that the RISHA method required a total cost of IDR 167,918,089.00 and an implementation duration of 56 working days, or 8 weeks. Meanwhile, the conventional method incurred a cost of IDR 172,562,093.00 and required 75 working days, or 11 weeks. Thus, RISHA construction provided cost savings of 2.69% and time efficiency of 25% compared with the conventional method. Although the cost of the RISHA superstructure was higher due to the use of precast components, significant savings in foundation and wall work, along with an accelerated construction timeline, made RISHA a more efficient overall alternative. Conclusion: Therefore, it can be concluded that the RISHA method offers advantages in cost and time efficiency for constructing a simple Type 36 house in the context of this study.